ANALISIS KEBIJAKAN PEMERINTAH MELAUI SURAT KEPUTUSAN BERSAMA (SKB) TIGA MENTERI TENTANG ATRIBUT DI LINGKUNGAN SEKOLAH PEMERINTAH - Bashori, Bashori (UIN Imam Bonjol Padang, 2021)
The emergence of Joint Decree (SKB) Number 219 year 2021 cannot be separated from the polemic at SMKN 2 Padang West Sumatra in 2021. The purpose of this study is to explore and analyze through an educational policy model approach. This research method uses a qualitative research model with a content analysis approach. Sources of research data use primary data from the SKB in this study, and are supported by various secondary data sources that are still relevant to this research study. The results of this study indicate that 1) The background for the issuance of the SKB 3 Minister's policy is the existence of problems that arise in the community about the attributes of the veil in government schools; 2) The formulation of the SKB 3 Ministerial policy through several stages, namely; problem formulation, forecasting (forecasting), policy recommendations, policy monitoring, and policy assessments; 3) The impact of the implementation of the 3 Ministerial Decree, namely; a) Revocation of various regulations issued by the Regional Government; b) Freedom in choosing to use attributes without religious distinctiveness or by using religious characteristics for both education and students; c) There are sanctions for violators of the SKB 3 Ministerial policy; d) Regional governments and government school principals will not issue policies that require or prohibit the use of school uniforms / attributes; and e)The development of tolerance, moderation, and mutual respect is not coercive within educational institutions. Â